Bite Reconstruction in the Aesthetic Zone Using One-Piece Bicortical Screw Implants - Stefan Ihde; Łukasz Pałka; Maciej Janeczek; Piotr Kosior; Jan Kiryk; Maciej Dobrzyński (Hindawi Limited, 2018)
The aim of this article was to present the clinical application of a new, smooth surfaced one-piece bicortical screw implant with immediate loading protocol. An 18-year-old, healthy male patient with a history of total dislocation and replantation of teeth 11 and 21 in early childhood was admitted to the clinic. Teeth 11 and 21 were extracted, and two long one-piece implants were inserted at extraction sockets in one surgical session under local anesthesia. Temporary composite crowns were placed in the patient on the same day. After 3 months, the single-phase two-layer impression was made and the composite crowns were replaced with metal-ceramic crowns. After 12 months, satisfactory aesthetic and functional results were obtained.